Simulating a nonspherical surface profile; The 9th Korea-Russia International Symposium on Science and Technology (KORUS 2005), June 26 - July 2, 2005, Novosibirsk State Technical University, Russia - Demin A. Yu. Anton Yurievich (2005, 2005)
Title screen